Insecticide Usage and Chemical Contamination Assessment in Asiatic Pennywort - S Bumroongsook (My University, 2017)
The insecticide usage in commercially grown asiatic pennywort plantations in Nakhonpatum and Nonthaburi province, Thailand was surveyed during January-June, 2016. The results showed that asiatic pennywort cuttworms was leaf destructive and caused the most damge to the production. The growers used organophosphate insecticides to control the caterpillars the most, followed by pyrethoid, abamectin, carbamate and organochlorine, respectively. The chemical contaminants of pennywort from 9 fresh markets in Bangkok was monitored, the result indicated that lead was not detected in the samples. The amount of arsenic was less than 0.075 mg / kg. The insecticide residue measurement of dicofol, chlorpyrifos and methidathion was 0.98, 2.84 and 0.46 mg / kg, respectively.
Keywords: Methidathion; Dicofol; Abamectin; Carbamate; Chlordane; Entomological Studies and Ecology